The Effect of Online Review on Consumer’s attitude and Purchase Intention towards automotive products - Tri Wahyuarini; Evi Sofiana; Syarifah Novieyana (Inovbiz: Jurnal Inovasi Bisnis, 2022)
This study was conducted to examine the effect of online reviews on consumer attitudes and buying interest in automotive products by adopting research by Sudirman (2018). Sudirman’s research examines the influence of online YouTube reviews about Toyota Rush on consumers buying interest mediated by consumer attitudes.The main construct of this study is electronic word of mouth variables in the form of online reviews of automotive products and consumers attitudes and buying interest. The objective of this research are: Firstly, whether there is a positive influence from electronic word of mouth (e-WOM) in the form of online reviews on social media platform: YouTube, Facebook and WhatsApp on consumer attitudes towards automotive products. Secondly, whether there is a positive influence of consumer attitudes towards automotive products on buying interest in automotive products. And the thirdly, whether there is a positive influence of electronic word of mouth in the form of online reviews on social media platform: YouTube, Facebook and WhatsApp on consumer buying interest in automotive products.To find out whether the goal is proven or not, hypothesis is used then tested empirically using regression with the help of SPSS Program.The result show that it is proven that there is a positive influence of e-WOM on consumer attitudes towards automotive products. This research also proves that there is a positive influence of consumer attitudes towards automotive products on the purchase intention of automotive products. This research does not prove that there is a positive effect of e-WOM on consumer interest in buying automotive products, but proves that the influence of e-WOM on buying interest in automotive products mediated by the variable of consumer attitudes towards automotive products.